Quality Evaluation of Bioplastic from Glutinous Rice Starch Reinforced with Bamboo Leaf Powder - Arifin, Uma Fadzilia; Adetya, Nais Pinta; Pambudi, Wisnu; Ratnaningsih, Wahyu (Universitas PGRI Madiun, 2022)
Plastics are widely used in various aspects of life due to their variety of superior properties. However, they contribute a negative impact on the environment, which leads to the search for an alternative solution such as the production of bioplastics as biodegradable plastics. Therefore, this study aims to evaluate the psycho-mechanic quality of bioplastic from glutinous rice starch reinforced with bamboo leaf powder. The bioplastic synthesis process was carried out using 0, 1, 3, 5, and 7% (w/w) variations of bamboo leaf powder on glutinous rice starch, respectively. The results showed that the best bioplastic composition was the addition of 3% (w/w) bamboo leaf powder to glutinous rice starch. This indicated that the addition of bamboo leaf powder in bioplastics can enhance the thickness, hardness, and tensile strength significantly. Meanwhile, the value of density, water vapor transmission rate, and elongation showed a slight increase, and the bioplastic also degraded more than 70% for 7 days.